Stability in the average quadratic for the harmonic oscillator with a random parameter - Bobrik , R. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Sufficient mean-square stability conditions of a harmonic oscillator whose random parameter is an Ornstein-Uhlenbeck process are obtained.